Associated Risk Factors of Asymptomatic Bacteriuria In Pregnancy - Shahid, Mahnoor; Mushtaq, Rubina; Jabeen, Nadia (Journal of Rawalpindi Medical College, 2026)
Objective: This study aimed to determine the prevalence of asymptomatic bacteriuria among pregnant women and to ascertain the associated risk factors. Methods: This cross-sectional study was conducted in Rawal Institute of Health Sciences, Gynae /Obs department from 1st Sept 2024 till 31st July 2025. A total of 300 pregnant women of any gestational age, attending their first antenatal visit, asymptomatic for urinary tract infection, were included. Patients with symptoms of acute urinary tract infection, on antibiotics for at least 72 hrs for any infection, acute or chronic kidney disease, or urinary stent were excluded. Midstream clean-catch sample collected for analysis and culture. Information on maternal demographics, obstetric history, and potential determinants of asymptomatic bacteriuria was systematically recorded. SPSS VS 25 was used for data analysis. Results: Prevalence of ASB in our study was 22%. Regarding socio-demographic factors of patients (300), the maximum number of cases, 48% presented between 26-32 years with a mean age of 28 years. Urban residents 77%, 48% matriculate, 71 % from the middle class, 68% had parity from 1-4, 52% presented in the 3rd trimester. The predominant pathogen isolated was E. coli in 78%. The principal maternal complication was preterm labor (11%), 14% developed p-pyrexia. Multivariate logistic regression confirmed significant associations of ASB with low socioeconomic status, low education, rural residence, parity >4, and recurrent UTI with a statistically significant p value<0.05. Conclusion: This study highlights a notable prevalence of ASB in pregnancy and underscores the importance of targeted screening for women with identifiable risk factors. Keywords: Asymptomatic bacteriuria, Infectious, Pregnancy Complications, Risk factors